Pulmonary involvement in polymyositis and dermatomyositis. (February 2009) - Tornling, Gööran; Fathi, Maryam; Lundberg, Ingrid E
Pulmonary complications play an important role in causing morbidity and mortality in myositis, and interstitial lung disease (ILD) has been reported in up to 65% of myositis patients. Clinical symptoms including cough and dyspnoea are common, but they are not reliable for ILD detection. The diagnosis should be based on pulmonary function tests, chest radiographs and high resolution computed tomography, which should all be regarded as standard procedures for the initial evaluation of all myositis patients. Biomarkers, in particular anti-aminoacyl tRNA synthetase antibodies, have been demonstrated to be useful in predicting the risk of ILD in patients with myositis. Glucocorticoids remain the mainstay of therapy in adult polymyositis and dermatomyositis patients with ILD, but most patients fail to fully respond to this treatment and require additional immunosuppressives such as methotrexate, cyclophosphamide, azathioprine and ciclosporin A. Other treatment options include intravenous γγ-globulins, tacrolimus and CD20 monoclonal antibodies. Myositis is closely related to the antisynthetase syndrome, which also includes manifestations such as ILDs, arthritis, Raynaud''s phenomenon, fever and mechanic''s hands. In this syndrome, ILD is often the first manifestation of a chronic inflammatory disease. There is now also accumulating data to support a role of a T-cell- and B-cell-mediated immune response in the development of ILD in patients with anti-tRNA synthetase autoantibodies.